Pengembangan Media Maket pada Materi Peninggalan Sejarah Hindu, Budha dan Islam, Kelas IV Sekolah Dasar - Mohammad Sofwan Raharjo; Tri Murti; Puri Selfi Cholifah (Universitas Negeri Malang, 2023)
Abstract: Learning in elementary schools requires appropriate media to facilitate teachers and students in achieving learning objectives. The purpose of this research is to produce social studies learning media products in the form of mockups on historical relics of Hindu, Buddhist and Islamic grade IV Elementary Schools that are valid according to media experts, material experts and users (teachers) and are interesting for students. In this type of research Research and Development using the ADDIE model and through 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. The results obtained from the validation of material experts are 91.6 percent, media experts are 81.25 percent, user 1 is 90 percent and user 2 is 95 percent. The test results of the attractiveness of the small group students were obtained at 92.59 percent and the large group obtained the results of 95.47 percent. From these results, if accumulated, the results can be used without revision and the media is interesting for students. Abstrak: Pembelajaran disekolah dasar memerlukan media yang tepat guna untuk memudahkan guru dan siswa dalam mencapai tujuan pembelajaran. Tujuan dari penelitian ini untuk menghasilkan produk media pembelajaran IPS berbentuk Maket pada materi peninggalan sejarah Hindu, Budha dan Islam kelas IV Sekolah Dasar yang valid menurut ahli media, ahli materi dan pengguna (guru) serta menarik bagi siswa. Pada penelitian ini berjenis Research and Development dengan menggunakan model ADDIE dan melalui 5 tahapan yaitu Analysis, Design, Development, Implementation dan Evaluation. Hasil yang diperoleh dari validasi ahli materi sebesar 91,6 persen, ahli media sebesar 81,25 persen, pengguna 1 sebesar 90 persen dan pengguna 2 sebesar 95 persen. Hasil uji coba kemenarikan siswa kelompok kecil diperoleh sebesar 92,59 persen dan kelompok besar diperoleh hasil sebesar 95,47 persen. Dari hasil tersebut jika diakumulasikan mendapat hasil dengan katergori dapat digunakan tanpa revisi dan media menarik bagi siswa.